Phenotypic Dissimilarities among Inbreds of Maize (Zea Mays L.) - Subedi, S.; Paudel, B.; Bhandari, B. (International Journal of Applied Sciences and Biotechnology, 2016)
For development of single cross hybrids in maize, developed inbreds must be evaluated for the determination of highly heterotic inbred combination (HIC). One of the best methodologies for determination of heterotic inbred combination can be multivariate analysis (MVA) or scales of phenotypic distance or dissimilarities or cluster diagram. For it, inbred must be observed for useful trait measurements. Accordingly, an experimental evaluation was conducted including promising 55 inbred lines of winter maize planting on Sep 3, 2015 at National Maize Research Program Rampur, Chitwan Nepal (NMRP/NARC). The distant inbred lines were determined through MVA. Single plot research technique was done where each inbred line was provided with 2 rows of 20 plants each. Data were taken for fifteen traits. By the use of MINITAB software, the data was analysed. Graphics of principle component analysis (PCA) cluster diagram (CD or dendogram) were constructed and phenotypic dissimilarities are examined.The distant inbreds RML-8, RML-88, RML-13, RML-103, RML-89, RML-102, RML-11, RML-17, RML-83,RML-98,RML-85,RML-86,RML-94 and RML-28 could be crossed with RML-75,RML-6,RML-68,RML-36 and RML-32 which could be used as tester inbred for heterotic hybrid combination. Similarly, RML-98, RML-85, RML-86, RML-94 and RML-28 could be crossed with RML-24, RML-96 and RML-99. Though distant inbred, RML-104 had less ASI but it wasn’t feasible to use for crossing due to higher anthesis tasseling interval. Int J Appl Sci Biotechnol, Vol 4(3): 359-364